The Influence of Competence and Training on Pokdarwis Performance through Community-Based Tourism (CBT) Empowerment in East Kutai Regency - Yanti Yanti; Titin Ruliana; Meiki Permana (Annals of Human Resource Management Research, 2026)
Purpose: This study examines the impact of competence and training on the performance of Pokdarwis (Community-Based Tourism Groups) through Community-Based Tourism (CBT)-based empowerment as a mediating variable in East Kutai Regency. Research Methodology: A quantitative approach with hypothesis-testing design was used. The population consisted of 20 Pokdarwis groups with 540 active members, and 268 respondents were selected through purposive sampling. Data were collected via structured questionnaires and analyzed using Partial Least Squares (PLS) with SmartPLS 3.0. Results: The study found that competence does not significantly affect Pokdarwis performance, while training has a positive and significant effect. Both competence and training significantly influence CBT-based empowerment, which in turn positively impacts Pokdarwis performance. The model's R² value shows that 55.7% of CBT-based empowerment and 50.5% of Pokdarwis performance are explained by the model. Conclusions: CBT-based empowerment mediates the relationship between competence, training, and Pokdarwis performance. Sustainable training programs and structured empowerment initiatives are essential to strengthen the capacity of local tourism groups. Limitations: The study is limited by its specific focus on East Kutai Regency and a relatively small sample size, which may affect the generalizability of the findings. Contributions: This research contributes to community-based tourism literature by highlighting the role of training and competence in enhancing the performance of local tourism organizations through empowerment. The findings provide valuable insights for tourism policymakers and practitioners.